2013
DOI: 10.1097/dcr.0b013e31828d02ba
|View full text |Cite
|
Sign up to set email alerts
|

Readmission for Dehydration or Renal Failure After Ileostomy Creation

Abstract: Hospital readmission due to dehydration or renal failure following ileostomy creation is common, with age >50 being the strongest predictor for renal failure. Appropriate strategies to decrease dehydration and renal failure following ileostomy creation need to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
95
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 22 publications
15
95
2
2
Order By: Relevance
“…The most common etiologies for readmission include postoperative infection, renal failure, and dehydration. The readmission rate for dehydration or renal failure within 30 days following ileostomy creation ranges from 17 to 36%, and an age of >50 years is an independent predictor of readmission for renal failure [15]. Consistent with our findings, the aforementioned observations indicate that ileostomy more frequently leads to renal insufficiency than colostomy does and significantly increases the readmission rate.…”
Section: Discussionsupporting
confidence: 88%
“…The most common etiologies for readmission include postoperative infection, renal failure, and dehydration. The readmission rate for dehydration or renal failure within 30 days following ileostomy creation ranges from 17 to 36%, and an age of >50 years is an independent predictor of readmission for renal failure [15]. Consistent with our findings, the aforementioned observations indicate that ileostomy more frequently leads to renal insufficiency than colostomy does and significantly increases the readmission rate.…”
Section: Discussionsupporting
confidence: 88%
“…Hanzlik et al have suggested that protocolized peri-operative teaching, such as the "Ileostomy pathway" which has been shown to reduce readmission rates in patients with new ostomies should be adopted in these cases. 16,17,22,[24][25][26][27] Of the post-operative complications, renal complications and urinary tract infections (7.6% each), were found to be significant risk factors for readmission and the similar findings were observed by Kassin et al as well. 3 Kelly et al also found that UTI was a significant factor for readmission.…”
Section: Discussionsupporting
confidence: 76%
“…Current literature reports adult readmission rates for dehydration after ileostomy creation near 20% [15]. Therefore, we do not appreciate a statistical or clinical difference between cohorts regarding rate of dehydration.…”
Section: Accepted Manuscriptmentioning
confidence: 85%